2018
DOI: 10.1088/1674-4527/18/12/148
|View full text |Cite
|
Sign up to set email alerts
|

A report on Type II X-ray bursts from SMC X-1

Abstract: We study RXTE PCA data for the high mass X-ray binary source SMC X-1 between 2003-10 and 2003-12 when the source was in high states. The source is found to be frequently bursting which can be seen as flares in lightcurves on an average of one in every 800 s, with an average of 4-5 X-ray burst per hour of type II. We note that typically burst was short lasting for few tens of seconds in addition few long bursts of more than hundred seconds were also observed. The flares apparently occupied 2.5% of the total obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…We present Be X-ray pulsar 4U 1901+03 analysis which has undergone short bursts of tens to hundreds of seconds. The burst of the X-ray pulsar can be due to instability in accretion disk burst (Taam et al 1988;Lasota & Pelat 1991;Cannizzo 1996) similar to the burst observed in other sources namely, SMC X-1, GRO J1744-28 and MXB 1730-355 (Moon et al 2003;Rai et al 2018;Fishman et al 1995;Lewin et al 1976). Pulse profiles show variation with both time and flux and are similar to that observed by (Lei et al 2009;Reig & Milonaki 2016;Ji et al 2020).…”
Section: Discussionsupporting
confidence: 77%
“…We present Be X-ray pulsar 4U 1901+03 analysis which has undergone short bursts of tens to hundreds of seconds. The burst of the X-ray pulsar can be due to instability in accretion disk burst (Taam et al 1988;Lasota & Pelat 1991;Cannizzo 1996) similar to the burst observed in other sources namely, SMC X-1, GRO J1744-28 and MXB 1730-355 (Moon et al 2003;Rai et al 2018;Fishman et al 1995;Lewin et al 1976). Pulse profiles show variation with both time and flux and are similar to that observed by (Lei et al 2009;Reig & Milonaki 2016;Ji et al 2020).…”
Section: Discussionsupporting
confidence: 77%
“…One of only a handful of SGXBs known to accrete via Roche lobe overflow, SMC X-1 exhibits persistent emission near or above its isotropic Eddington luminosity of L Edd ∼ 1.3 × 10 38 erg s −1 (for a mass of ∼ 1.1 M , as reported by van der Meer et al 2007) varying between L X (2 − 12 keV) ∼ 10 37 erg s −1 in the low state and luminosities in excess of 5 × 10 38 erg s −1 (2 − 12 keV), more than three times its Eddington luminosity, in the high state (Bonnet-Bidaud & Klis 1981). In addition to this persistent emission, SMC X-1 has been shown to exhibit type II X-ray bursts with durations of tens of seconds (Angelini et al 1991;Rai et al 2018). Its near-to super-Eddington luminosity places the source in a middle ground between less luminous Be/X-ray binaries (BeXB), which exhibit a range of persistent X-ray luminosities from 10 32 erg s −1 (Tomsick et al 2011) up to 10 35 erg s −1 (Reig & Roche 1999), and brighter ultraluminous X-ray pulsars (ULXPs).…”
Section: Introductionmentioning
confidence: 99%
“…We take a constant persistent count rate of B = 170 cts/s/pcu [49], though in reality the persistent emission varies with the superorbital period; e.g., the count rate in Fig. 4 is a bit lower, while even higher rates have been observed [50]. Future observations should focus on high points in the superorbital period to obtain the best lensing sensitivity.…”
Section: Existing Data From Rxtementioning
confidence: 99%